The Effect of Coastal Dike and Retention Pond Performance on Flood and Tidal Control in Pekalongan - Adhitya Gilang Irawanto; Joko Nugroho; Adi Prasetyo (Jurnal Teknik Sipil, 2023)
Abstract. Pekalongan is one of the areas located in the north of Java Island. The main problem in Pekalongan is tidal flooding. This tidal flood worsens when there is a high discharge in the river. For this reason, the government built a Coastal Dike and a Retention Pond to overcome these problems. The concept of this system is to create a coastal dike that crosses the river to eliminate tidal effects. The retention pond is located along the coastal dike to accommodate the discharge from the river, then the water will be pumped downstream of the river. This study aims to obtain pump operating time for each pump built in this system to reduce the flood elevation of Q25 to – 0.5 m in the retention pond. One dimensional flow modeling was used in the approach with the Hydrologic Engineering Center-River Analysis System (HEC-RAS) 6.0 model. This research shows that the pump operating time for the Silempeng and Sengkarang pumps is 150 hours. The addition of Mrican pumps and flap gates can reduce pump operating time to support the success of Coastal Dike and Retention Ponds in controlling floods and tidal in Pekalongan. Keywords: Tidal flood, coastal dike, retention pond, pump.